PENGARUH ANYAMAN BAMBU AMPEL SEBAGAI TULANGAN ALTERNATIF PELAT BETON TERHADAP KUAT LENTUR DAN POLA RETAK - Nanin Meyfa Utami; Erno Widayanto; Annisa Rahmadina; Trismi Ansyah Yogi Pratama (Politeknik Negeri Jakarta, 2026)
Concrete is a material composed of cement, fine aggregate, coarse aggregate, and water. It has high compressive strength but low tensile strength; therefore, reinforcement is required to improve flexural performance. Steel reinforcement is commonly used, but its cost and availability make alternative materials attractive. This study investigates ampel bamboo weaving as a substitute for steel reinforcement in concrete slabs. Bamboo strips with dimensions of 56 × 2 × 0.2 cm were soaked for three weeks and woven into four configurations: dense single-cross weave, loose single-layer weave, loose double-layer weave, and a steel D8 reference slab. Thirteen specimens were tested, consisting of three specimens for each bamboo variation and three steel-reinforced comparison specimens. Flexural capacity and crack pattern were evaluated through experimental testing and yield-line theory. The loose double-layer weave produced the highest average flexural capacity of 4.85 kN·m, while the steel-reinforced slab reached 8.90 kN·m. Observed cracks generally formed an intersecting pattern that initiated at the center of the slab and propagated toward the edges, which is consistent with yield-line theory. The results show that ampel bamboo weaving can be used as an alternative reinforcement, although its capacity remains below that of steel.